Pleomorphic hyalinizing angiectatic tumor with a sarcomatous component recurring as high-grade myxofibrosarcoma - Kazakov, Dmitry V; Pavlovsky, Michal; Mukensnabl, Petr; Michal, Michal (Pathology international, 2007)
Pleomorphic hyalinizing angiectatic tumor (PHAT) of the soft tissue is a rare distinctive tumor listed as a benign neoplasm in the new World Health Organization classification. It may recur and most reported recurrent tumors retained the typical morphological appearance of PHAT; rare tumors recurred with the appearance of a sarcoma. Reported herein is an additional example of recurrent PHAT, but in contrast to the previously described cases the present tumor morphologically qualified as a sarcoma from the very beginning; it recurred as a high-grade myxofibrosarcoma. A 76-year-old woman presented with a solitary subcutaneous tumor in the axilla that was surgically removed. Seven months later, the patient experienced a local recurrence. Microscopically, the typical features of PHAT were identified in the initial lesion, namely hyalinized, fibrin-containing vessels and pleomorphic stromal cells; there were areas of hemorrhage and necrosis. Additionally, peripherally located areas of the tumor manifested highly pleomorphic cells with frequent atypical mitoses, producing a sarcomatous appearance. The mitotic index in the sarcomatous part was 1/10 high-power fields (HPF). Hyalinized, fibrin-containing vessels were absent in these sarcomatous areas, and the stroma was myxoid. The recurrent lesion was composed of large highly pleomorphic oval, round, spindled or bizarre cells with a high mitotic rate, ranging from 3/10 HPF to 7/10 HPF. The neoplastic cells were arranged haphazardly in a myxoid matrix. Hyalinized, fibrin-containing vessels typical for PHAT were absent. PHAT may be more aggressive than previously thought, and PHAT may encompass a morphological spectrum of the lesion ranging from benign to malignant.
Keywords: senioři; Fibrin; fibrin; dermatofibrosarkom; Sarcoma; Skin Neoplasms; Hyalin; Necrosis; Neoplasm Recurrence, Local; lokální recidiva nádoru; hyalin; Dermatofibrosarcoma; ženské pohlaví; Humans; nádory kůže; sarkom; Skin; nekróza; Female; Aged; kůže; lidé